(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
This paper challenges the concept of hatred as foundational within a Cartesian self. I will contend that instead it represents a choice made by people who see themselves in a weak and helpless position. The argument is developed within the psychology of personal constructs (Kelly, 1955), and draws in Mair’s (2011) ’community of self’ metaphor. The implications of this new formulation are discussed.